An Intelligent Model Using Excel Spread Sheet in a Manufacturing System - Ho , Kok Hoe; Kanesan , Muthusamy; Harikrishnan , Kanthen (2011)
The research integrates the combination of mathematical modeling and intelligent modeling concept to represent a manufacturing system in the Excel spread sheet interface. The mathematical modeling uses two types of approaches, which use IE variables and the development of mathematical theorem using deduction methodology from the dynamic manufacturing system. Mathematical language and mathematical reasoning technique through programming in spread sheet are used to build an intelligent modeling system which optimizes targeted inventory level in order to response without human involvement.